Globalization and the third world : issues, prospects, and challenges - Vijapur, Abdulrahim P.; Doraiswamy, Rashmi; Academy of Third World Studies (New Delhi : Manak Publications, 2009)
Contributed articles presented at an in-house seminar organized by MMAJ Academy of Third World Studies, Jamia Millia Islamia during 6-7 November, 2006.
Includes bibliographical references and index.
Keywords: Globalization -- Developing countries -- Congresses